Ergonomic analisys in creation and development of textile industry - Souza, Josiane Aparecida Cardoso de; Melo, Igor José Machado de; Venturini, Gabriela Rezende de Oliveira; Mazini Filho, Mauro Lúcio (Brazilian Journal of Production Engineering, 2022)
As a major generator of jobs, the textile industry has great prominence in the world market and along with the growth of organizations, comes the concern with the health of the worker so as not to lose productivity. Thus, workers in the area are more exposed to risks of developing occupational diseases arising from inappropriate positions, repetitive movements, internal pressure for results, among others. This article ergonomically evaluated a sector of Creation and Development of a Textile Industry through the application of a checklist to check ergonomics in general and consequently the health of the worker. A Nordic questionnaire was also applied to analyze the parts of the body that employees feel the most pain. The results revealed the need for an integrated action program that acts mainly on factors such as "Layout" and "Keyboard and Keyboard Support" and "Work System". Consequently, the most affected places were the wrists and the back, which highlights the importance of measures such as exchange or adaptation of items and breaks and the participation of workers in ergonomic education.